Islamic Knowledge Transmission in Salafiyah Pesantren: An Analysis of Sorogan, Wetonan, and Bandongan Learning Methods - Muhammad Sanusi; Abd. Mukti; Usiono Usiono (Dirasah International Journal of Islamic Studies, 2026)
This study aims to analyze the process of Islamic knowledge transmission in Salafiyah pesantren through the application of traditional learning methods such as sorogan, wetonan, and bandongan. The research employs a qualitative approach through field research conducted at Musthafawiyah Purbabaru Islamic boarding school in North Sumatra, Indonesia. Data were collected through in-depth interviews with teachers and students, direct observation of learning activities, and analysis of documentation related to educational practices within the pesantren. The findings reveal that the transmission of Islamic knowledge in Salafiyah pesantren is carried out through a classical curriculum centered on the study of kutub al-turāṡ (classical Islamic texts) combined with traditional pedagogical methods. The sorogan method plays an important role in strengthening students’ individual competence in reading and understanding classical texts through direct interaction with teachers. Meanwhile, the wetonan and bandongan methods serve as collective learning mechanisms that enable teachers to transmit religious knowledge to large groups of students systematically. These methods serve not only as instructional strategies but also as mechanisms for preserving the intellectual traditions of Islamic scholarship within the pesantren environment. The study concludes that the sustainability of Islamic knowledge transmission in Salafiyah pesantren depends on the consistent use of traditional learning methods, the authority of religious teachers, and the continued use of classical Islamic texts as primary sources of learning.